Morphological and molecular data for three species of the Microphallidae (Trematoda: Digenea) in Australia, including the first descriptions of the cercariae of Maritrema brevisacciferum Shimazu et Pearson, 1991 and Microphallus minutus Johnston, 1948 - Kudlai, Olena; Cutmore, Scott C; Cribb, Thomas H (Folia parasitologica, 2015)
Cercariae and metacercariae of three species of the Microphallidae Travassos, 1920 were found in snails and crustaceans from tributaries of the Brisbane River, Queensland, Australia. Specimens of Maritrema brevisacciferum Shimazu et Pearson, 1991 and Microphallus minutus Johnston, 1948, which have previously been reported in Queensland, were found as cercariae in the tateid gastropod Posticobia brazieri (Smith) and as metacercariae of M. brevisacciferum in the atyid shrimp Caridina indistincta Calman and of M. minutus in the parastacid crayfish Cherax dispar Reik. Combined analysis of morphological and molecular data, based on newly generated ITS2 and partial 28S rDNA data, linked cercariae and metacercariae for both species. This is the first report of the first intermediate hosts of M. brevisacciferum and M. minutus. Infections of another unidentified microphallid metacercariae, Microphallidae gen. sp., were found in P. brazieri and C. indistincta. The sequences of metacercarial isolates from both hosts were identical. The data on the Microphallidae from Australia and species that develop in freshwater invertebrates were examined in detail.
Keywords: Brisbane River; rDNA sequences; freshwaters; morphology; life cycle; larval stages